Peningkatan Pemahaman Tentang Peralihan Hak Waris Tanah Di Kelurahan Sekip Kecamatan Limapuluh Kota Pekanbaru - Yeni Triana; Handana Handana (Asosiasi Dosen Akuntansi Indonesia, 2021)
Land and also the property above it are objects of an inheritance. This article emphasizes problems concerning land as an object of inheritance that is transferred from someone to their heir (land inheritance rights) by doing legal counseling based on consent between writer and writer partner which is the Head of Urban-Village of Sekip, Limapuluh Sub-District. The lack of understanding of the community regarding the mechanism of transferring land inheritance rights certainly has the potential to cause problems, such as the certificate of the land that will be the inheritance merely converts to 1 (one) of their names, while in fact there is more than 1 (one) heir. In addition, if the heir uses Notary service in managing their transfer of land inheritance rights to a notary who is not credible and has an unfavorable track record so that it can potentially incur costs that are not needed by the heirs or even worse which can lead to BPHTB tax evasion. Thus, after the program is implemented, it is hoped that partners will gain the correct understanding and have knowledge about the transfer of land inheritance rights. Based on the results obtained from this activity, the participants have felt the benefits, namely gaining additional knowledge and understanding of the transfer of the land inheritance rights. It was concluded by the community service team after comparing the results of the initial test (pre-test) and the final test (post-test) by asking questions (questionnaires) before and after giving the material. In conclusion, the problems faced by the target audience before giving the material were a lack of understanding of the mechanism of transfer of the land inheritance rights. Based on the explanation of the community service team in the implementation of this. activity, there has been an increase in the target audience's understanding of the transfer of the land inheritance rights.